Chemical Castration Sanctions Against Pedophiles Based on Mashlahah Perspective - Mujahidul Haq, Ahmad Hamdan; Salenda, Kasjim; Muhammad Bakri, Muammar (Pascasarjana UIN Alauddin Makassar, 2023)
This study discusses the chemical castration sanctions against pedophiles. The main problem in this study is how are the sanctions for chemical castration in Law No. 17 of 2016 concern Child Protection? and what are the sanctions for chemical castration against pedophiles in Law No. 17 of 2016 concerning Child Protection based on Mashlahah perspective? The methodology used was field research, using qualitative methods with a juridical and normative approach. Then, the data collection methods were analysis, interviews with the ulama (Indonesian Ulema Council) of South Sulawesi Province, and documentation. The data processing and analysis techniques had several stages: data reduction, data presentation, data editing, data analysis, and conclusion. The results showed that: 1) Chemical castration sanctions in Law No. 17 of 2016 concerning Child Protection is a sanction in the form of injecting a chemical substance that aims to suppress sexual desires towards perpetrators of sexual crimes against children (pedophiles). The chemical castration sanction in the Law is an additional criminal sanction that is imposed at most two years after the perpetrator has served the main sentence in the form of imprisonment; 2) Chemical castration sanctions in Law No. 17 of 2016 concerning Child Protection are categorized as mashlahah mulghah by the ulama, it refers to rejected mashlahah because there is an argument for the prohibition of castration in the hadith and ijma' of the ulama.